Prediction of springback in V-bending and design of dies using finite element simulation. (6th October 2010) - Kumar, Apurv; Viswanath, P.; Mahesh, K.; Swati, M.; Kumar, P.M.; Abhijit, A.; Singh, Swadesh
The main application of sheet bending is in automobile industries. The phenomenon of springback depends on the elastic recovery and the extent of deformation that is provided on the material. In this research, Springback is being calculated in 90° V-bended sheets using finite element simulation. In bending of thin sheets, Springback causes the angles finally produced to be different from what was intended. Finite Element Method (FEM) is adopted to determine the amount of springback occurring in V-bending of sheet metal of a particular material, and from the results of simulation, dies are designed to produce 90° bend in the sheet.